IMPLEMENTASI METODE DEEP LEARNING DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MA NEGERI 2 REMBANG, JAWA TENGAH - Azim Dias Al-Choiri; Laily Masruroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional teaching methods in Islamic Religious Education (IRE) in madrasahs, such as lectures and rote memorization, often result in superficial student comprehension and restricted use of Islamic principles in day today activities. This project's goal is to find out how the Deep Learning method may be applied to enhance students' comprehension of Islamic Religious Education. at MA Negeri 2 Rembang, Central Java. Specifically, the research explores how Deep Learning is used during the educational process, how it enhances students understanding, and identifies the supporting and inhibiting factors impacting its executionThis study employs a qualitative technique and a case study design. Interviews with the vice principal for curriculum affairs and Islamic Religious Education are among the main sources of data teachers, and eleventh-grade studentsData collection methods include observation, in-depth interviews, and documenting. analysis follows a systematic process involving data display, data reduction, and drawing/verifying conclusions, backed via triangulation to guarantee the accuracy of the dataThe findings demonstrate that the use of the Deep Learning method at MA Negeri 2 Rembang is conducted through three primary phases: joyful learning, attentive learning, and purposeful learning. This approach has proven effective in significantly enhancing students’ understanding across cognitive, affective, and psychomotor domains. Students demonstrate improved critical thinking skills, increased active participation, and a stronger the capacity to connect Islamic values in real-world situations. In conclusion, Deep Learning is an effective pedagogical strategy for enhancing pupils' comprehension of Islamic Religious Education, as it fosters a holistic comprehension of Islamic teachings that integrates knowledge, practice, and moral character development. Supporting factors include progressive madrasah policies, teacher training, and student enthusiasm, while challenges involve limited instructional time and diverse student abilities